The Application of DNA Barcoding in Crustacean Larvae Identification from the Zhongsha Islands, South China Sea - Xu, Lei; Wang, Xuehui; Huang, Delian; Wang, Lianggen; Ning, Jiajia; Li, Yafang; Liu, Shuangshuang; Du, Feiyan (Frontiers in Marine Science, 2022)
Marine crustaceans are known as a group with high morphological diversity and great economic value. Most species have planktonic larval stages that are difficult to identify at species level using traditional approaches because of insufficient morphological diagnostic characters or taxonomic descriptions. We used DNA barcoding and molecular species identification to investigate the species diversity and distribution of crustacean larvae found in waters of the Zhongsha Islands, South China Sea. In total, 108 sequences were obtained from crustacean larvae that were collected at the islands in 2019 using vertical hauls between depths of 5 and 200 m. The molecular classification approaches confirmed that 108 sequences represented crustaceans typical to the South China Sea, with 70 species identified, representing 43 genera, 23 families, and 4 orders. However, the cytochrome c oxidase subunit I gene sequences of only 27 species identified from the larval samples matched with sequences taken from previously described adults available in a database (GenBank). Comparison of K2P distances yielded a notable gap of 3.5–10.7% between intraspecific and interspecific distances across the sequence dataset. More than 80% of the crustacean larvae species belonged to the order Decapoda, and they displayed marked differences in their distributions at the Zhongsha Islands. The orders Calanoida and Amphipoda were represented by the fewest species, which were recorded only at the edge of the Zhongsha Atoll.